CITY TOURISM TRANSPORTATION SERVICES: A CASE STUDY OF DOUBLE-DECKER BUS ROUTE 5 IN SPECIAL CAPITAL REGION OF JAKARTA - Bhakti Nur Avianto; Erina Oktaviani (NATAPRAJA, 2020)
The Government of Special Capital Region of Jakarta until the end of 2019 seeks to revitalize tourism program by launching double-decker bus. But this implementation, there are still problems with a low level of passenger services, shelters without seats, small bus AC rooms, and responsiveness of PLB officers is still low. Purpose of this study is to explore values bus transportation services that are predicted for quality and service satisfaction. The approach used is survey methodology with results show that bus transportation service predicted values for service quality is transparency aspect; accountability; and conditional; all service products used by passengers. While, participatory aspect; equal rights; and the balance of rights and obligations, predicted to impact in service satisfaction received—recommendations for improvements in service quality, especially provision facilities and ease accessibility. While improvement service satisfaction is improved, safety on buses and empathy PLB officers in responding services.